Area of Skin Numbness after Less Invasive Total Knee Arthroplasty Surgery: A prospective study - Limtrakul, MD, Arak; Tanavalee, MD, Aree; Nghamukos, MD, Srihatach; Tantawisut, MD, Saran (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The objective of this study was to assess the area of skin numbness after less invasive total knee arthroplasty (TKA) surgery and to compare the area of skin numbness between groups in which the skin incision length was less than or equal to 10 cm and more than 10 cm. Methods: A prospective study was conducted. 58 TKAs who had undergone primary TKA for osteoarthritis were recruited into this study. All patients were performed by a less invasive surgical technique. The necessity for extending the incision length depended on skin tension, intraoperatively of each patient. Based on the skin incision length, the population was categorized into two groups. Patients with skin incision lengths of less than or equal to 10 cm formed group A (29 patients), whereas patients with a skin incision length of more than 10 cm formed group B (29 patients). The areas of skin numbness were measured with the knee in full extension using a blunt pin for pin-prick sensation. The measurement area of skin numbness was performed at 2 weeks, 1 month, 3 months, and 6 months postoperatively. Results: In group A, the mean area of skin numbness was 31.74 cm2, 30.94 cm2, 29.58 cm2 and 9.60 cm2 at 2 weeks, 1 month, 3 months, and 6 months postoperatively, respectively. In group B, the mean area of skin numbness was 51.14 cm2, 39.50 cm2, 27.67 cm2 and 11.83 cm2 at 2 weeks, 1 month, 3 months, and 6 months postoperatively, respectively. The area of skin numbness decreased over time in both groups. Conclusions: This study demonstrated the area of skin numbness after TKA depends on the length of skin incision and that the skin sensation improved with time.